Comparative evaluation of choroidal thickness in hypertensive individuals and healthy controls using optical coherence tomography - Jaimy Ann Philip; Charmaine Bridgette Solomon; Sanaa Mohammed Konnakkodan; A Arun Kumar; Ashik C. Refeek; Shabeena Basheer (Kerala Journal of Ophthalmology)
Purpose: This study aimed to assess the impact of hypertension on choroidal thickness by comparing hypertensive patients with age-matched healthy individuals. Methods: A cross-sectional comparative study included 62 individuals (31 each in the hypertensive and control groups, aged 30–70). Choroidal thickness was measured at subfoveal, 500 µm nasal, and 500 µm temporal to the fovea using optical coherence tomography (OCT). Statistical analysis employed independent-samples t-tests, and correlations were evaluated with Pearson’s coefficients. Results: Subfoveal choroidal thickness was similar in hypertensives and normals (294.02 ± 61.27 and 295.86 ± 50.86, respectively). Nasal and temporal thickness was significantly reduced in hypertensive patients (256.38 ± 59.32 and 269.53 ± 69.50) compared with controls (285.34 ± 51.37 and 280.34 ± 55.85). Subfoveal thickness had a weak positive correlation with mean blood pressure (MBP) (Pearson’s coefficient 0.150), while nasal thickness had a significant but weak negative correlation with MBP (Pearson’s coefficient -0.73). No significant correlation existed between hypertension duration and choroidal thickness. Conclusion: The study revealed reduced nasal and temporal choroidal thickness in hypertensive individuals compared with age-matched healthy subjects. Subfoveal thickness in hypertensives showed a significant but weak positive correlation with MBP, and nasal thickness had a negative correlation with MBP.